Q. 1

(i) 3a2b, -4a2b, 9a2b

= 3a2b + (-4a2b) + 9a2b

= 3a2b – 4a2b + 9a2b

= 3a2b

(ii)

= a + a - a

Taking L.C.M 3, 5 , 5 is 15

=11

=

=

(iii)

= 4xy2 – 7x2y + 12x2y – 6xy2 – 3x2y + 5xy2

= 4x2 + 12x2y – 3x2y – 7x2y – 6xy2 + 5xy2

= 3xy2 + 2x2y

(iv)

=

= + +

= - +

(v)

= xy + y + + y - - xy

= + +

= - -

(vi)

= x3 - x2 + + x3 + x2 – x + + x2 - x – 2

= x3 + x2 - +

= 5x3 + x2 -

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Subtract:

NCERT - Mathematics Exemplar

Take away:
</p
RD Sharma - Mathematics

Subtract 3x-4y-7zRD Sharma - Mathematics

Subtract:

RD Sharma - Mathematics

If we subtract -3NCERT - Mathematics Exemplar

<spanNCERT - Mathematics Exemplar

State whether theNCERT - Mathematics Exemplar